2014
DOI: 10.1109/mcom.2014.6979964
|View full text |Cite
|
Sign up to set email alerts
|

IEEE 802.11ad: directional 60 GHz communication for multi-Gigabit-per-second Wi-Fi [Invited Paper]

Abstract: INTRODUCTIONWith the worldwide availability of a large swath of spectrum at the 60 GHz band for unlicensed use, we are starting to see an emergence of new technologies enabling Wi-Fi communication in this frequency band. However, signal propagation at the 60 GHz band significantly differs from that at the 2.4 and 5 GHz bands. Therefore, efficient use of this vast spectrum resource requires a fundamental rethinking of the operation of Wi-Fi and a transition from omnidirectional to directional wireless medium us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
277
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 514 publications
(300 citation statements)
references
References 4 publications
0
277
0
2
Order By: Relevance
“…It specifies the physical layer and MAC layer in the frequencies above 40 GHz and supports wireless transmission with multi Gbit/s data rate but with limited range [6]. Current research has shown that the point-topoint systems using mmWave either in V-band (57-64 GHz) or E-band (71-76 and 81-86 GHz bands) can achieve high data rates (up to 10 Gbit/s), while reducing interference over long distance.…”
Section: Mmwave Wireless Communicationmentioning
confidence: 99%
“…It specifies the physical layer and MAC layer in the frequencies above 40 GHz and supports wireless transmission with multi Gbit/s data rate but with limited range [6]. Current research has shown that the point-topoint systems using mmWave either in V-band (57-64 GHz) or E-band (71-76 and 81-86 GHz bands) can achieve high data rates (up to 10 Gbit/s), while reducing interference over long distance.…”
Section: Mmwave Wireless Communicationmentioning
confidence: 99%
“…Thus, at these portions of the spectrum, bandwidth is at a premium, mainly for outdoor communication. For indoor communication, 60 GHz ISM (industrial, scientific, and medical) unlicensed band is worldwide available and its use for Wi-Fi communication has been standardized as the IEEE 802.11ad specification [31,32], offering up to 7 Gbps throughput and allowing the use of very small and low-cost antennas [33,34].…”
Section: Networked Robotics Applicationsmentioning
confidence: 99%
“…In particular, we name an MC-IS network equipped with directional antennas as an MC-IS-DA In this paper, we consider a flat-top antenna model [9], [38], [42], in which sidelobes and backlobes are ignored. Our antenna model assumes that a directional antenna gain is within a specific angle, i.e., the beamwidth of the antenna, which is ranging from 0 to π.…”
Section: A Using Directional Antennas In Mc-is Networkmentioning
confidence: 99%